Prediction of Streamflow of the Anai-Weir Catchment Using Both the SWAT and Mock Models - Mas Mera; Siti Hawa Binti Yusmardi; Junaidi Junaidi (Journal of Applied Agricultural Science and Technology, 2023)
This research focuses on predicting the streamflow of the Anai-weir catchment using the SWAT (Soil and Water Assessment Tools) and Mock models. The catchment studied is approximately 34,024 ha wide. The rainfall and climatological data were collected from the three nearest rainfall stations, namely Kandang IV (13.8 km far), Kasang (15.2 km far), and Sicincin Stations (11.2 km far), from 2010 to 2019. The first research methodology is to delineate the catchment, form a Hydrologic Response Unit (HRU), and then enter the climatological data into the SWAT model to estimate the daily streamflow. This daily streamflow is then averaged over a semi-monthly period. The second research methodology is to estimate an evapotranspiration depth based on the climatological data using the Modified Penman method, and then predict the semi-monthly average-daily streamflow using the Mock model. The results obtained from both methods are then compared with the Anai-weir AWLR-data. The average results from each method, namely, the SWAT model, the Mock model, and the AWLR data have the same tendency, but the Mock model results are closer than the SWAT model results to the AWLR data. This indicates that the Mock model is more suitable than the SWAT model for the existing data conditions. Even though the SWAT model considers more variables than the Mock model does.